Businesses' attitudes towards corruption in the EU (Publications Office of the European Union, 2024)
This Eurobarometer survey, first conducted in 2013, and repeated in 2015, 2017, 2019 and 2023, is designed to explore the level of corruption perceived and experienced by businesses employing one or more persons in the following six key sectors: energy, mining, oil and gas, chemicals; healthcare and pharmaceutical; engineering and electronics, motor vehicles; construction and building; telecommunications and information technologies; and financial services, banking and investment. The survey covers a range of areas, including:  Businesses' perception of the level of corruption in their country  The prevalence of practices leading to corruption  How corruption is investigated, prosecuted and sanctioned  Problems encountered when doing business  Corrupt practices in public tender and public procurement procedures.
10.2837/144519
Keywords: Graue Literatur; public procurement; public contract; corruption; fraud against the EU; European undertaking; abuse of power; fight against crime; crime; patronage; economic consequence; nepotism; application of the law; report